Changes in sensory attributes of condiment prepared from Thai pangus (Pangasianodon hypophthalmus) during storage at different temperatures: Changes in sensory attributes of fish condiment (Journal of the Bangladesh Agricultural University, 2019)
For value addition, only developing different products from fish muscle /mince is not enough, as maintenance of proper storage condition to keep the sensory attributes in acceptable range and marketing of the developed products very important. Therefore, the study was carried out to observe the changes in sensory attributes of fish condiment prepared from Thai pangus mince, stored at different temperatures. In the development of product and different analysis standard procedures were followed with some modification in the processes. In this study, a detailed survey on consumers’ preference to fish condiment was done at Kamal-Ranjit Market of Bangladesh Agricultural University (BAU), Kewatkhali, Mymensingh town and Faculty of Fisheries (BAU). This study revealed that the sensory attributes of fish condiment decrease throughout the storage period irrespective of storage temperatures (room temperature, 28°C to 32°C; refrigeration temperature, 5°C to 8°C and frozen temperature, -18°C to -20°C). At low temperatures, this product may remain in acceptable condition for more than 120 days. The consumers’ preference study showed that most of the respondents liked fish condiment and also they showed their interest to buy from shop and shop owners showed interest to sell this product. The average price offered by the consumers for the fish condiment was 18.52 taka and by the shopkeepers, 19.51 taka for 10g of condiment in each pack; which were much higher than the production cost. The cost profit analysis showed that the margin of profit for the fish condiment was 35.14%.J Bangladesh Agril Univ 17(3): 402–408, 2019